Market development for genetically modified foods [ - Evenson, Robert E. [ (Robert Eugene)] , 1934-; Santaniello, V. (CABI, 2001)
This work addresses key issues in market development for genetically modified foods. It focuses on: consumer reactions to GM food information; regulatory issues; farmer acceptance of biotech products; changes in industrial organization in life science ad food sectors.